2012
DOI: 10.4161/isl.18675
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecule CADM1 contributes to gap junctional communication among pancreatic islet α-cells and prevents their excessive secretion of glucagon

Abstract: Keywords: connexin, cell-cell interaction, Necl-2, hyperglucagonemia, diabetes mellitus, SynCAMCell adhesion molecule-1 (CADM1) is a recently identified adhesion molecule of pancreatic islet a-cells that mediates nerve-a-cell interactions via trans-homophilic binding and serves anatomical units for the autonomic control of glucagon secretion. CADM1 also mediates attachment between adjacent a-cells. Since gap junctional intercellular communication (GJIC) among islet cells is essential for islet hormone secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
(46 reference statements)
1
19
0
Order By: Relevance
“…Such selectivity is appropriate for proper islet functioning, particularly since beta and alpha cells function antagonistically under most conditions. Gap junctions have been claimed to connect different islet cell types [258], which are occasionally coupled in culture [259, 260]. However, direct evidence that alpha and beta cells make bona fide gap junction plaques has not yet been provided, and tracer studies do not support the occurrence of a large coupling between these cells [261263].…”
Section: Cell Interactions In the Endocrine Pancreasmentioning
confidence: 99%
“…Such selectivity is appropriate for proper islet functioning, particularly since beta and alpha cells function antagonistically under most conditions. Gap junctions have been claimed to connect different islet cell types [258], which are occasionally coupled in culture [259, 260]. However, direct evidence that alpha and beta cells make bona fide gap junction plaques has not yet been provided, and tracer studies do not support the occurrence of a large coupling between these cells [261263].…”
Section: Cell Interactions In the Endocrine Pancreasmentioning
confidence: 99%
“…In T2DM pancreata, the decrease in full-length CADM1 was associated with its absence from the cell membrane in both alpha and beta cells (Table 1). Previously, we reported that CADM1 contributes to gap junctional communication among mouse islet alpha cells and that decreased expression of CADM1 on the cell membrane of mouse alpha cells resulted in the supernormal secretion of glucagon, suggesting that mouse CADM1 may serve as a volume limiter of glucagon secretion by sustaining alpha cell-cell attachment necessary for efficient gap junctional communication [17]. Similarly in human T2DM pancreata, downregulation of full-length CADM1 may impair gap junctional communication among alpha cells and thus underlie the hyperglucagonemia often observed in T2DM patients [40].…”
Section: Discussionmentioning
confidence: 95%
“…In mice, CADM1 expression is restricted to alpha cells, whereas it is expressed equally in the four cell types (alpha, beta, D, and PP) that constitute human islet cells [16]. CADM1 appears to play a significant role in hormone secretion by mediating islet cell-cell and islet cell-nerve interactions through trans -homophilic binding [16], [17]. Recent studies have shown that CADM1 expression is regulated by post-transcriptional mechanisms, including glycosylation and proteolytic cleavage, referred to as shedding [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…3B). As in ␣-cells then, CADM1 in islet ␤-cells appears to function as an inhibitor of hormone release (23).…”
Section: Cadm Expression In Human and Rat Isletsmentioning
confidence: 99%
“…In ␣-cells, CADM1 helps constrain glucagon secretion (23). Enhanced insulin secretion in CADM1 global knockout mice suggests that CADM1 similarly inhibits insulin exocytosis (38).…”
mentioning
confidence: 99%